2021
DOI: 10.1021/acsanm.1c00111
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Carbon Nanofibers Prepared with Ni and Ni/Graphitic Carbon Nanoparticle Catalysts for Glycine Detection Using Surface-Enhanced Raman Spectroscopy

Abstract: The combination of a noble metal with a carbon nanomaterial for surface-enhanced Raman scattering (SERS) has been commonly explored using metal-outside surface decoration to achieve a dominant electromagnetic enhancement mechanism. The use of a non-noble metal encapsulated inside carbon nanofibers (CNFs) for SERS is an interesting field of research because its heterogeneous structure possibly amplifies charge transfer, which induces the chemical enhancement mechanismbased SERS phenomena. This study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The intensities of some characteristic peaks of quinine obviously varied (as indicated by the black arrows), and the strong single peak at 1362 cm −1 was cracked into a shoulder peak with peak points at 1362 and 1380 cm −1 . More importantly, the characteristic peaks belonging to Glu appeared, including 565 (δ ip N−H), 995 (υC−O), and 1021 cm −1 (υC−N), 36 and the detailed peak assignments are listed in Table S6. All these spectral results demonstrated that Glu enantiomers were effectively captured by the AuNP−quinine complex and were located in the strong enhancing hotspot regions on the NPoM platform.…”
Section: Analyticalmentioning
confidence: 99%
“…The intensities of some characteristic peaks of quinine obviously varied (as indicated by the black arrows), and the strong single peak at 1362 cm −1 was cracked into a shoulder peak with peak points at 1362 and 1380 cm −1 . More importantly, the characteristic peaks belonging to Glu appeared, including 565 (δ ip N−H), 995 (υC−O), and 1021 cm −1 (υC−N), 36 and the detailed peak assignments are listed in Table S6. All these spectral results demonstrated that Glu enantiomers were effectively captured by the AuNP−quinine complex and were located in the strong enhancing hotspot regions on the NPoM platform.…”
Section: Analyticalmentioning
confidence: 99%
“…The stacked graphene sheets of diverse shapes can generate more edge sites on the outer wall of CNFs, and this is the primary factor that making a distinction of CNFs from CNTs. ,, CNFs are longer than the CNTs, have a larger diameter, and grow at comparatively lower temperatures but do not have a hollow cavity. , The 1D structures of CNFs reduce the diffusion lengths of ions in radial orientation and provide abundant active sites and voids to load active material. ,, CNFs have somewhat lower surface areas as well as electrical conductivities compared to CNTs but still have lower manufacturing costs and compatibility with industrial mass production and are easy to disperse, making them potential candidates for energy storage applications and power management apart from other uses in sensors, tissue engineering, and more.…”
Section: Cnfs: Structure Synthesis and Propertiesmentioning
confidence: 99%
“…Imaging of neurotransmitters heavily relies on in situ hybridization against the target gene of interest, calcium indicators, transgenic reporters, and protein detection with immunohistochemistry. , The majority of the studies for the detection of glycine have been performed under in vitro and ex vivo conditions that do not provide a complete picture of what actually happens within the body. On the other hand, the in vivo studies have used high-end spectroscopic imaging, genetically encoded fluorescent sensors, riboswitches, and microneedle biosensors, all of which require state-of-the-art facilities (see Table S1 in the Supporting Information for a performance comparison). In light of these concerns, we have created a novel fluorescent probe that can detect glycine and have attempted to monitor the levels of glycine in vivo in the brainstem and spinal cord .…”
Section: Introductionmentioning
confidence: 99%